(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The cloud security is to get to the data by approved clients by anyplace and whenever idea. Here, the data encryption and key encryption procedures are utilized to get the data. Where, the data encryption will work under ECC (elliptical curve cryptography) algorithm, to lessen the data bits. It stores in public cloud. The key encryption method conveys by the honey encryption algorithm. This honey encryption algorithm stores the double encrypted key in the fog cloud and the garbage value returns to the unapproved personates. Here the private key will create to the receiver’s E-mail ID associated with the registration. Indeed, even the sender won’t know about the key which was created. On the off chance that the receiver side issue happens, the exchange get come up short and self-transaction happens.